Performance of asymmetric supercapacitor fabricated with perovskite‐type Sr2+‐incorporated LaMnO3 (La0.7Sr0.3MnO3) nanostructures in neutral 1M Na2SO4 aqueous electrolyte. (8th April 2021) - Roy, Atanu; Cancino‐Gordillo, Francisco Enrique; Saha, Samik; Pal, Umapada; Das, Sachindranath
Summary: Strontium (Sr) incorporated LaMnO3 (La0.7 Sr0.3 MnO3 ) nanoparticles have been synthesized by ball‐milling‐assisted solid‐state reaction to study their performance as electrode material for energy storage applications. The La0.7 Sr0.3 MnO3 nanoparticles exhibit superior electrochemical performance in neutral aqueous electrolyte (1 M Na2 SO4 ) in comparison to LaMnO3 and SrMnO3 nanoparticles. This neutral electrolyte provides relatively higher ionic conductivity and viscosity compared to the ionic liquids and a wider potential window compared to the alkaline electrolytes. Electrochemical study of the electrodes prepared using La0.7 Sr0.3 MnO3 nanoparticles reveals pseudocapacitive behaviors with fast reversible Faradaic charge storage, which plays a key role in charge storage. The composite materials exhibit highest specific capacitance of 393.5 F g −1 at a scan rate of 2 mV s −1 . Asymmetric supercapacitors fabricated using La0.7 Sr0.3 MnO3 nanoparticle and activated carbon operates over a wide potential window of 1.8 V, and it reveals high specific capacitance (197 F g −1 ) as well as high capacitive retention (87%) even after 4000 charge–discharge cycles. Abstract : Mechano‐chemically synthesized La0.7 Sr0.3 MnO3 nanoparticles have been studied in neutral aqueous electrolyte for supercapacitive application. Electrochemical study reveals that the rapid reversible Faradaic reaction plays the key role in charge storage process. Asymmetric supercapacitor with the as synthesized nanoparticles as positive electrode and activated carbon as negative electrode exhibits excellent energy and power density.